Digital entrepreneurship among higher education students - Gunaseelan, Khemaalatha; Subramaniam, Tamil Selvan; Lai, Chee Sern; Jabor, Mohd Khata; Rathakrishnan, Geetha (Human Resource Management Academic Research Society, 2022)
Since the digital entrepreneurship and the industry 4.0 have been considered as the emerging technologies in the Malaysia, their emphasis to ascertain the exposure of the students in the Malaysian higher education will suffice. The digital entrepreneurship has faced several challenges such as lack of proper skills by the staff and lack of proper facilities to assist in the instruction process. However, the policies proposed and the increased number of universities and colleges in Malaysia appreciating the program have emphasized its adoption. The implementation of the Higher Education Entrepreneurship Development Policy has contributed to many benefits. The paper focusses on the digital entrepreneurship appreciation in the Malaysia higher education mostly by students and the intensification by the ministry of higher education.